2014
DOI: 10.1016/j.pharep.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective activity of aliskiren, a renin inhibitor in cyclosporine A induced hypertensive nephropathy in dTG mice

Abstract: A correlation between pharmacological, biochemical and histological findings has been established in mouse model. The present findings have indicated the renoprotective activity of aliskiren in CsA induced hypertensive nephropathy, which may be due to its antihypertensive, anti-inflammatory as well as anti-apoptopic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Following 28 days of BID 10 mg/kg ALS oral dosing in C57BL/6-(hREN)/(hAGT) double transgenic mice with concurrent coadministered subcutaneous cyclosporine A (20 mg/kg), urinary KIM-1 (approximately 3.25 ng/mL) was not significantly changed ( p > 0.05) compared to the control group. 33 In our study, we may have only observed a transient increase in KIM-1 through NP usage.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Following 28 days of BID 10 mg/kg ALS oral dosing in C57BL/6-(hREN)/(hAGT) double transgenic mice with concurrent coadministered subcutaneous cyclosporine A (20 mg/kg), urinary KIM-1 (approximately 3.25 ng/mL) was not significantly changed ( p > 0.05) compared to the control group. 33 In our study, we may have only observed a transient increase in KIM-1 through NP usage.…”
Section: Discussionmentioning
confidence: 57%
“…This change may also be timedependent as the Saraswat et al study showed that BUN (22.33 + 0.56 mg/dL) was not significantly changed (p > 0.05) compared to the control group. 33 In another study, Sprague-Dawley rats treated with daily intramusculuar gentamicin (100 mg/kg) and ALS (25 mg/ kg) via osmotic pump for 14 days, plasma creatinine concentration was reduced compared to gentamicin alone. 34 Further, in five out of six nephrectomized rats treated with oral 10 mg/kg ALS over 4 weeks, plasma creatinine was significantly reduced (p < 0.05) compared to nephrectomized controls.…”
Section: Discussionmentioning
confidence: 97%
“…14 In the literature, data are scarce addressing the beneficial effect of Alisk in CNI nephrotoxicity. One of the two related studies has investigated only blood and urine samples in CyA-treated hypertensive mice, 48 the other report focusing on Tac-induced nephropathy has examined whole kidney samples to prove attenuation of oxidative stress. 49 However, none of them focused on the source of renin or explained the subsequent vascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many research studies have been conducted to suggest supplemental agents to confer additional protection for the kidney against CYCinduced toxicity. These supplemental agents may include herbal drugs [3][4][5] , endothelin-1 receptor antagonists 6 , antihypertensive drugs or β-blockers [7][8][9] , NADPH oxidase activity inhibitor 10 , antioxidants 11 , omega-3 fatty acids 12 , apelin peptide 13 , and/or renin inhibitor 14 . Gender and sex hormones are also important factors that influence the effects of CYC [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%